The Relationship of Family Support, Internal Motivation and Incentives with The Performance of Posyandu Cadres in Karawaci District, Tangerang City - Lina Mardianti; Fathiyati; M. Adila Rossa; Al-Bahra (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2024)
The aim of this research is to determine the relationship between family support, internal motivation and incentives on the performance of posyandu cadres in Karawaci District, Tangerang City. The research design used is correlational analytics with a quantitative approach. This research was conducted at Posyandu in the Karawaci District, Tangerang City, which was carried out from March to May 2022. The population in this research was all Posyandu cadres in the Karawaci District, Tangerang City in 2022, namely 60 people. The number of samples in this research was 60. This result concluded that most respondents had good performance, namely 71.67%, family support was 78.33%. There is a relationship between family support and the performance of Posyandu cadres. Most respondents had internal motivation as much as 53.33%. There is a relationship between internal motivation and the performance of Posyandu cadres. Most respondents have received incentives, namely 70.00%. There is a relationship between incentives and the performance of Posyandu cadres.